ANALISIS TEKNIK DASAR BULUTANGKIS SEBAGAI FAKTOR PENDUKUNG KUALITAS PERMAINAN ATLET - Anjelika Adisti Sitepu; Azril Himawan; Benny Johan Hutagalung; Marwadinur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Badminton is a sport that requires speed, accuracy, body coordination, tactical awareness, and mastery of basic techniques. In athlete development, technical ability becomes an important foundation because it influences movement efficiency, shot accuracy, game consistency, and the ability to reduce unforced errors. This study aims to analyze basic badminton techniques as supporting factors for athletes’ game quality. The method used in this study is a qualitative method with a literature review approach. Data were collected from open-access scientific journals, academic articles, and credible sources published mainly between 2022 and 2026. The data were analyzed descriptively by reviewing, comparing, and interpreting relevant literature related to grip, footwork, serve, lob, dropshot, smash, forehand, backhand, and other technical elements in badminton. The results show that basic techniques play an important role in supporting athletes’ performance because they are closely related to shot control, court coverage, movement balance, and tactical execution. Good mastery of basic techniques also helps athletes maintain consistency during matches and adapt to different game situations. Therefore, basic technical training should be conducted systematically, repeatedly, and in line with athletes’ physical and tactical development.